Functional neuroimaging of the somatosensory system with Ultra-high-field fMRI and MEG - Wang, Fan (2012)
Multimodal neuroimaging using a combination of Magnetoencephalography (MEG) and ultra-high-field fMRI are used in order to gain further insight into the neural oscillations and haemodynamic responses in the somatosensory cortex.